1919
DOI: 10.1002/jez.1400280305
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of life of Tribolium confusum apparently due to small doses of x‐rays

Abstract: Prolongacihn de la vida de Tribolium confusum debida aparentemente a pequeiias dosis de 10s rayos X.En un trabajo publicado anteriormente (Journ. Exp. Zool., t. 22, m6m. 3, hbril 1917) se describieron experimentos que demuestran: 1) Que una cantidad suficiente de rayos X pueden acortar la vida de Tribolium confusum, y, 2 ) Que la duracihn de la vida despues de la accihn de dichos rayos puede expresarse por una f6rmula matemhtica, cuya derivacihn tebrica fu6 expuesta en dicho trabajo. El presente trabajo cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1924
1924
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…This has been recognized for nearly a century as Davey [33,34] published the findings of an extremely well-designed series of experiments that demonstrated that X-ray exposure enhanced the lifespan of the confused beetle ( Tribulium confusum ). While the striking findings of Davey [33,34] would fail to inspire researchers to extend his research efforts in the first half of the 20th century, numerous investigators did develop an interest in aging research by the late 1950s, using insect models and ionizing radiation.…”
Section: Hormesis: Enhancing Longevitymentioning
confidence: 99%
“…This has been recognized for nearly a century as Davey [33,34] published the findings of an extremely well-designed series of experiments that demonstrated that X-ray exposure enhanced the lifespan of the confused beetle ( Tribulium confusum ). While the striking findings of Davey [33,34] would fail to inspire researchers to extend his research efforts in the first half of the 20th century, numerous investigators did develop an interest in aging research by the late 1950s, using insect models and ionizing radiation.…”
Section: Hormesis: Enhancing Longevitymentioning
confidence: 99%
“…He therefore suggested in 1919 that a low level of ionising radiation might stimulate rather than depress biological functions and health. Davey's view was based on experimental work which he had carried out and as a result of which he had been able to verify a prolongation of life in PriboIium confusum populations exposed to small doses of X-rays (Davey, 1919). Together with Atkinson, who had even earlier in 1898 made the observation that r6ntgen-irradiated algae grew faster than their non-irradiated controls (Atkinson, 1898;Webster, 1993), Davey may have been the first to speak in favour of the idea of radiation hormesis.…”
Section: History and Origin Of The Concept Of Hormesismentioning
confidence: 99%
“…One of the earliest studies to show the life prolonging effects of irradiation were performed on flour beetle, Tribolium confusum, in which repeated exposure of beetles to low doses of Xrays (100-500 mA/min at 25 cm at 50 kV) reduced their death rates as compared with unexposed organisms [52,53] . Similar observations on the lifeextending effects of gamma-rays and X-rays on flour beetles were later reported by other authors [54,55] .…”
Section: Radiation Hormesis In Insectsmentioning
confidence: 99%